Increasing the Impact of Policy Analysis – by Asking It to Do Less. Issue 5 (20th October 2018) - Shapiro, Stuart
Abstract: More than 50 years ago, Charles Lindblom outlined a critique of "comprehensive-rational analysis", the idea that policy problems should be thoroughly analyzed before solutions are implemented. Despite the influential criticism, policy analysis has spread across the globe. In the cases of cost‒benefit analysis, risk assessment, and environmental impact assessment, these analyses have attempted to be both comprehensive and rational. This article discusses research into these three forms of analysis in practice in the United States. Interviews were conducted with dozens of practitioners of these three forms of analysis in an attempt to understand when they have successfully influenced policy decisions and when they have failed to do so. Based on these interviews and a series of case studies, a series of reforms to the use of analysis are proposed. These reforms share the characteristic of asking analysis to do less, to make it simpler for the public to understand, to place deadlines on its completion, allowing analysts to work independently of their agencies, and using panels of affected interests to react to and help refine analyses.